Zdravljenje fibromialgije - Zaletel, Marjan (Rehabilitacija (Ljubljana), 2010)
Fibromyalgia is a chronic syndrome that is characterized by widespread body pain. The prevalence of fibromyalgia syndrome in the general population is estimated to be 2-7%. Chronic pain is often associated with comorbidities suchas depression, chronic fatigue, anxiety. With the new evidence regarding the pathophysiology of the fibromyalgia syndrome, it has been suggested that it may be one of the neuropathic pain syndromes. Although the pathogenesis is not completely understood, it has been suggested that peripheral or central hyperexcitability at the level of spinal cord or brainstem is involved. Drugs that are successful in the treatment of neuropathic pain syndromes have also been tested for fibromyalgia. These medications include antidepressants and other neuromodulators, as well as other analgesics. Dopamine agonists are suitable for patients with fibromyalgia especially if they report restless legsyndrome. The use of conventional analgesics is not recommended. Nonfarmacological measures are also important in fibromyalgia syndrome.
Keywords: Analgesics, Opioid; Analgetiki opioidni; Antidepresivi; Antidepressive Agents; Diagnosis; diagnostika; Dopamine Agonists; Dopaminski agonisti; drug; Drug Therapy; Fibromialgija; Fibromyalgia; kronična bolečina; Neuralgia; Nevralgija; nevropatska bolečina; therapy; zdravila; zdravljenje